2009
DOI: 10.1089/jop.2007.0125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prostaglandin Analogs and Prostamide on Central Corneal Thickness

Abstract: Topical therapy with prostaglandin analogs and bimatoprost is associated with CCT reduction over a period of at least 8 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…Most of the recent studies have showed that prostaglandin analogues could decrease the central corneal thickness (CCT) values [13][14][15][16][17][18][19]. Lee and Cho [13] observed that latanoprost significantly reduced CCT in normal-tension glaucoma patients after 5 years of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the recent studies have showed that prostaglandin analogues could decrease the central corneal thickness (CCT) values [13][14][15][16][17][18][19]. Lee and Cho [13] observed that latanoprost significantly reduced CCT in normal-tension glaucoma patients after 5 years of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, prolonged exposure to prostaglandin analogues seems to induce structural changes at the level of the corneal stroma, and numerous studies have revealed that chronic treatment with prostaglandins reduces central corneal thickness. 15,[19][20][21] This could also affect the results obtained when translated to the real situation of the treatment of patients with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…The PGAs have also been shown to decrease the central corneal thickness (CCT) [6,[14][15][16][17][18][19][20][21], and because Goldmann applanation tonometry underestimates the IOP in eyes with thinner corneas [22][23][24][25], questions have arisen about the accuracy of the IOPs measured after the use of PGAs.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies on the effect of different PGAs on the CCT [6,[18][19][20][21], which PGA would reduce the CCT the most has not been determined.…”
Section: Introductionmentioning
confidence: 99%